PENGARUH NPL, ROA, DAN CAR TERHADAP PBV PADA BANK BUMN - Siti Maimunah; Tasya Fahtiani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The main objective of the company is to maximize the value of the company that is used as a measure of the success of the company. Price to Book Value is a measurement of company value by looking at how much the market values the book value of its shares. Financial performance is one of the factors that influence company value. The better the financial performance, the better the value of the company. This study aims to examine the effect and to explain the effect of non-performing loans, return on assets and capital adequacy ratios simultaneously to the price to book value of state-owned banks listed on the Indonesia Stock Exchange in 2009-2017. This research was conducted at state-owned banks (Persero) listed on the IDX for the period 2009-2017. The sample used was 4 companies with saturated sample method. The analytical method used is quantitative analysis, in the form of testing hypotheses using statistical tests. The data were tested using Eviews version 10 with the selection of models in panel data, testing classical assumptions with normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, panel data regression analysis, and hypothesis testing using the t test, F test and R2 test. The partial test results with the t test of obtaining non-performing loans have a negative effect on price to book value, return on assets and capital adequacy ratio do not affect price to book value. Simultaneously non-performing loans, return on assets and capital adequacy ratios affect price to book value.